1996
DOI: 10.1002/(sici)1097-0061(199612)12:15<1555::aid-yea43>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of a 39 411 bp DNA fragment covering the left end of chromosome VII of Saccharomyces cerevisiae

Abstract: We have sequenced a DNA fragment of 39 411 bp which includes part of the left telomere of chromosome VII of Saccharomyces cerevisiae. We have identified 19 open reading frames (ORFs); six correspond to known yeast genes (ADH4, FZF1, HKB, RTG2, HFM1 and PDE1), nine have similarity with other genes and four exhibit no significant similarity with any known gene. The average size of these ORFs seems to be related to their location, the eight ORFs nearest the telomere being shorter than the 11 others. These two gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Subcloning and partial DNA sequencing of the MER3 plasmid revealed that the suppression activity resides in a 4.8 kb Eco RI‐ Sal I fragment (pTN84, Figure 1B), including a hypothetical open reading frame (ORF), YGL251c (Coissac et al ., 1996). However, YGL251c with an additional upstream region of 508 bp (pTN66) was not sufficient for the suppression.…”
Section: Resultsmentioning
confidence: 54%
“…Subcloning and partial DNA sequencing of the MER3 plasmid revealed that the suppression activity resides in a 4.8 kb Eco RI‐ Sal I fragment (pTN84, Figure 1B), including a hypothetical open reading frame (ORF), YGL251c (Coissac et al ., 1996). However, YGL251c with an additional upstream region of 508 bp (pTN66) was not sufficient for the suppression.…”
Section: Resultsmentioning
confidence: 54%
“…In this study, we identified 32 probe sets that detected increased levels of the RNA products of repeated genes located in the sub-telomeric repeats near chromosome ends. The probe sets, which corresponded to genes at one or both ends of 15 out of the 16 haploid chromosomes, include representatives of the PAU [48], DUP380 [49], DAN [50], MAL [51], AAD [52,53], and YRF [54] multi-gene families. Most of these transcripts were predicted to be indirect targets of NMD (the exceptions could be false discoveries).…”
Section: Functional Relationships Among Nmd Targetsmentioning
confidence: 99%